2018
DOI: 10.1051/matecconf/201815902052
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Dye Sensitized Solar Cells (DSSCs) Using β-Carotene Pigment Based Natural Dye.

Abstract: Abstract. The adsorption characteristic of natural dye has been studied on harvesting light using purification process. The purification process used for separation pigment photosynthesis of syngonium leafs was called fractionation. The first fractionation of the dye contains pigment of β-carotene . The absorpton spectrum of β-carotene has been investigated by using Uv-Vis spectroscopy. The Fourier Transform Infrared revealed that the binding of the dye was on the surface of TiO2. Analysis absorbance and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…absorbs in the green part of the solar spectrum, thus has been studied along with TiO 2 nanocatalyst for increasing its light-harvesting capacity and thus increasing hydrogen production. [28][29][30] β-Carotene displays an absorption maximum at 453 and 484 nm 31 and hence have been sensitized on TiO 2 Solar Cells to study and increase the efficiency 32 extensively. Following this, in the current study, we have demonstrated the efficiency enhancement of hematite nanoarchitectures with β-Carotene coating in the form of a 2-fold increase in the photocurrent density magnitude.…”
mentioning
confidence: 99%
“…absorbs in the green part of the solar spectrum, thus has been studied along with TiO 2 nanocatalyst for increasing its light-harvesting capacity and thus increasing hydrogen production. [28][29][30] β-Carotene displays an absorption maximum at 453 and 484 nm 31 and hence have been sensitized on TiO 2 Solar Cells to study and increase the efficiency 32 extensively. Following this, in the current study, we have demonstrated the efficiency enhancement of hematite nanoarchitectures with β-Carotene coating in the form of a 2-fold increase in the photocurrent density magnitude.…”
mentioning
confidence: 99%
“…(Table 6) shows the performance of DSSCs using carotenoid extracts from achiote seeds [105], Curcuma longa [143], golden trumpet [107], gardenia yellow [144], tomatoes [145], Syngonium sp [146], walnuts [147] and Gardenia blue [144] as photosensitizers. The relatively poor performance of DSSCs containing carotenoids as DS is likely due to the extensive conjugated double bond system that can hold the excited electron by formation of many stable resonance forms there by reducing the chance of electron jump to the photoanode.…”
Section: Fig 2 J-v Characteristic Curve Of the Dssc Performance [33]mentioning
confidence: 99%